Necessary conditions to implement innovation in remote networked schools: The stakeholders' perceptions - Sandrine Turcotte; Christine Hamel (The Canadian Network for Innovation in Education (CNIE), 2008)
Remote Networked Schools (RNS) is an initiative by the Quebec Ministry of Education, Leisure and Sports (MELS) to investigate solutions that the use of information and communication technologies (ICT) can offer for the preservation of small rural schools in Quebec, Canada. The implementation of RNS mobilized then - as it still does now - the local capacity for innovation of all the stakeholders involved in this networking effort to improve learning. Building on Donald P. Ely's work (1990; 1999), this paper presents the results of an investigation of the RNS educational stakeholders' perceptions of the importance of the conditions that facilitate the implementation of educational technology innovations for the success of RNS in their locations. Les conditions nécessaires à l'implantation de l'innovation de l'École éloignée en réseau: la perception des intervenants Résumé: L'École éloignée en réseau est une initiative du Ministère de l'Éducation, du Loisir et du Sport du Québec (MELS), qui a comme objectif d'explorer ce que l'usage des technologies de l'information et de la communication (TIC) peut offrir pour la sauvegarde des petites écoles rurales au Québec, Canada. L'implantation de l'École éloignée en réseau a mobilisé (et continue aujourd'hui) la capacité locale, pour l'innovation, de tous les intervenants impliqués dans cet effort de mise en réseau pour améliorer l'apprentissage. Partant des recherches de Donald P. Ely (1990; 1999), ce texte présente les résultats d'une étude sur la perception des intervenants impliqués dans l'École éloignée en réseau, quant à l'importance des conditions facilitant l'implantation d'innovations technologiques afin que cela soit un succès dans leur communauté.